Civil wars in Africa - Kalu, Kelechi Amihe; Kieh, George Klay, 1956- (Lexington Books, 2022)
"This book argues that civil wars in Africa stem from the contradictions and crises that have been generated by the post-colonial state as the result of the adverse effects of colonialism and the failure of successive generations of African leaders to lead the process of changing the state's nature, character, and mission"--